Some things get better with age: differences in salicylic acid accumulation and defense signaling in young and mature Arabidopsis - Carella, Philip; Wilson, Daniel C.; Cameron, Robin K. (Frontiers in Plant Science, 2015)
In Arabidopsis, much of what we know about the phytohormone salicylic acid (SA) and its role in plant defense comes from experiments using young plants. We are interested in understanding why young plants are susceptible to virulent strains of Pseudomonas syringae, while mature plants exhibit a robust defense response known as Age-Related Resistance (ARR). SA-mediated signaling is important for defense in young plants, however, ARR occurs independently of the defense regulators NPR1 and WHY1. Furthermore, intercellular SA accumulation is an important component of ARR, and intercellular washing fluids from ARR-competent plants exhibit antibacterial activity, suggesting that SA acts as an antimicrobial agent in the intercellular space. Young plants accumulate both intracellular and intercellular SA during PAMP- and Effector-Triggered Immunity, however, virulent P. syringae promotes susceptibility by suppressing SA accumulation using the phytotoxin coronatine. Here we outline the hypothesis that mature, ARR-competent Arabidopsis alleviates coronatine-mediated suppression of SA accumulation. We also explore the role of SA in other mature-plant processes such as flowering and senescence, and discuss their potential impact on ARR.